2021
DOI: 10.3390/rs13152905
|View full text |Cite
|
Sign up to set email alerts
|

Through-Wall Multi-Subject Localization and Vital Signs Monitoring Using UWB MIMO Imaging Radar

Abstract: Radar-based non-contact vital signs monitoring has great value in through-wall detection applications. This paper presents the theoretical and experimental study of through-wall respiration and heartbeat pattern extraction from multiple subjects. To detect the vital signs of multiple subjects, we employ a low-frequency ultra-wideband (UWB) multiple-input multiple-output (MIMO) imaging radar and derive the relationship between radar images and vibrations caused by human cardiopulmonary movements. The derivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The electromagnetic wave-based bio-radar shows advantages in non-contact, non-invasion of privacy, and strong scalability. It has been extensively studied to search for the post-disaster survivor, monitor sleep, evaluate drivers' health in vehicles, and detect vital signs through walls [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The electromagnetic wave-based bio-radar shows advantages in non-contact, non-invasion of privacy, and strong scalability. It has been extensively studied to search for the post-disaster survivor, monitor sleep, evaluate drivers' health in vehicles, and detect vital signs through walls [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave imaging systems span a wide range of applications such as concealed weapon detection [ 1 ], medical imaging [ 2 ], through-the-wall detection [ 3 ], non-destructive testing [ 4 ], etc. In recent years, these systems have drawn significant attention owing to their lower cost and compact size.…”
Section: Introductionmentioning
confidence: 99%
“…A through-wall radar (TWR) is one of the radar applications emitting electromagnetic waves that can penetrate the wall and receive reflections from certain objects behind the wall [1]. TWR is used to generate good wall penetration by working on very wide bandwidths, thus having the potential to detect small displacements, such as chest wall movement in breathing [2].…”
Section: Introductionmentioning
confidence: 99%
“…Breathing detection radar using ultra-wideband impulse radar (UWB) has also been discussed in [6], [7]. Meanwhile, in [8], breathing detection experiments with UWB MIMO imaging radar were shown. From the study, results showed that radar could detect vital signs of breathing behind walls.…”
Section: Introductionmentioning
confidence: 99%